Emergomyces africanus: The Mimicking Fungus - Ameshin Moodley; Anisa Mosam; Nelesh P. Govender; Yesholata Mahabeer; Antoinette Vanessa Chateau (MDPI AG, 2019)
A 31-year-old HIV-seropositive woman from Durban, KwaZulu-Natal, South Africa, presented with a 3-month history of widespread umbilicated and ulcerated skin papules, plaques, and nodules. The skin lesions were biopsied and sent for histology and fungal culture; the cultured isolate was referred for molecular identification. Histology, fungal culture, and molecular testing confirmed that the dimorphic fungal pathogen Emergomyces africanus had caused a disseminated mycosis.